The Concept Of Kafa’ah in Fathul Mu’in: It’s Application and Relevance To The Household Integrity Of The Mayangan Community In Jember - Indy Kamaliyah; Qurrotul Ainiyah; Siti Roudlotul Hikamah (Mauriduna : Journal of Islamic Studies, 2025)
The research aims to find out whether the concept of kafa’ah in the book of Fathul Mu’in is still relevant for the dynamic Mayangan community. This research focuses on the application of the concept of kafa’ah can maintain the integrity of the household of the Mayangan community in Jember. This research method uses a phenomenological approach to understand the experience of the Mayangan community in applying Zainuddin's concept of kafa’ah. The findings show that: first, the majority of the Mayangan community applies the concept of kafa’ah in the book Fathul Mu’in. Some interpret kafa’ah as equality in education, religion, and descent. Some understand compatibility in thinking. Second, there are two categories of people's understanding of the concept of kafa’ah: The first category consists of people who actively recite and study the book of Fathul Mu’in, and the second category is people who understand through informal oral delivery. The five criteria of kafa’ah in the book of Fathul Mu’in are very relevant for the people of Mayangan who have experienced a change in religious mindset to materialism. Therefore, it is morally necessary to place religious intelligence and morals as a priority for choosing a life partner for the integrity of the household and for building a healthy civilization.